Zajęcia umuzykalniające w świetlicy szkolnej = Musical classes in the school room - Lewandowska, Maria (Zielona Góra: Uniwersytet Zielonogórski, Wydział Pedagogiki, Psychologii i Socjologii)
Daycare is a special place in the school structure. In spite of changes in school systems, the main functions remain constant: caring, education, development and preparation for participation in culture. The text focuses on the opportunities and needs of the latter to show the value of the activities of this sphere of child development.
Keywords: świetlica szkolna; zajęcia umuzykalniające; school room; music lessons